The Team-Mate Identification (TM-ID) Test: Effect of participant and situation familiarity on response accuracy and latency - Steel, K.; Adams, R.; Canning, C.; Eisenhuth, J. (International Journal of Sports Science and Coaching, 2010)
In field and pool sports, players' running or swimming motor patterns appear to characterise them, and these `gait signatures` may aid in identifying players as team-mates. If this identification process was sufficiently brief to be relevant in ball sports, training to improve familiarity with team-mates' movement patterns may improve team performance. We examined time for Team-Mate Identification (TM-ID) decisions under different circumstances. 6 water-polo players (team-mate participants) and 6 club swimmers (unknown distractors) were filmed sprint swimming past two video cameras, one above and one below the water surface. The resulting footage was edited into two randomised series of video-clips. The water-polo players then viewed the clips and determined whether each observed swimmer was a team-mate or not, in the fastest possible time. Participants were faster with an overwater than an underwater view, significantly better than chance at identifying their team-mates, and did so in a mean time of 381 ms, which is within the normal window of time where expert sports people might be required to make time-stressed decisions.